Developing talent while promoting positive youth development: A balancing act - Fraser-Thomas, J.; Beesley, T.; Dickler, L.; Harlow, M.; Mosher, A.; Preston, C.; Wolman, L. (Routledge handbook of talent identification and development in sport, 2017)
In recent years, a growing interest in talent identification and development among high perform ance athletes has trickled down to children and youth in grassroots-level sports. With this has com e an increased focus on fostering talent among children and youth, leading to concerns surrounding children`s physical, psychological, social, and cognitive development. While many models of talent development embrace a simplistic physiological approach, frameworks are evolving to integrate the developing child into broader sport structural and organizational processes (Harwood & Johnston, 2016; Vierimaa, Erickson, & Cote, 2016). Cobley (2016) proposes that youth talent be conceptualized as a combination of youths`particular skills and qualities, grounded in the complex interaction of their individual characteristics, specific sport tasks, social environment, and policy priorities that underpin elite sport. However, despite the commonly held assumption that sport (at any level) is as a vehicle of psychosocial development (e.g., character-building), many have argued that the act of participation in sport alone is insufficient to produce identifiable outcomes (Fraser-Thomas, Cote, & Deakin, 2005; H olt & Neely, 2011). Further, the potential conflict between the goals of talent development (i.e., optim al performance), and youths` overall healthy development (i.e., positive youth development; PYD) has garnered growing attention as an issue of concern (Fraser-Thomas & Strachan, 2015; Gould, Collins, Lauer, & Chung, 2007).